Inspection Of Drill Bit Point Angle Using Image Processing Method - Ahmad Yusni, Amira Syuhadah (Universiti Sains Malaysia, 2018)
This research presents the inspection of drill bit point angle using a digital microscope and based on computer measurement which is by using image processing method. This project is to support Spirit Aerosystems Sdn. Bhd. in determining the lifespan of a drill bit and to provide a system that can detect wear or changes in the drill bit geometry specifically, point angle. Images of wear drill bit are captured and later on analyzed using MATLAB software to measure the point angle. There are two lighting setups used in this project which are focused light and ring light. Both setups are set to create backlight effect in order to enhance the edges of the drill bit. Besides having two setups of lighting, two methods of analyzing the data also presented in this thesis. The first method is binarization method and the other one is by using Sobel filter method. Both methods showed a similar trend of results where the system is capable of detecting the changes in point angle. This project is divided into two parts which are the hardware and software part. For the hardware, a close setup is designed and fabricated meanwhile for the software part, the images need to be imported into MATLAB software to be analyzed by both methods. The algorithm used is being referred to an example given by Math Work and being adapted into this project to suits the objective of this project. Within this project, we could observe the changes in the drill bit point angle by using both binarization and Sobel filtering methods.